Ethical Policy in Pawn: The Government Pawnshops Service in Late Colonial Java, 1900-1940 - Abdul Wahid (Lembaran Sejarah, 2012)
From an economic point of view, pawnshop has an important function as a micro-credit institution, especially for those living in the rural areas where access to capital market is often limited. In Java, pawnshop business has existed since the VOC period in the eighteenth century, but it only really burgeoned under the colonial state administration in the early twentieth century. In such a long period, pawnshop business shifted in nature from a private economic activity during the nineteenth century to a public service in the early twentieth century. The introduction of the Ethical Policy in 1901 brought the pawnshop government service into new direction; it became an instrument of welfare program to provide popular credit for indigenous population in rural areas that helped to free them from excessive usurious practices and indebtedness to illegal moneylenders. This paper argues that the operation of this government enterprise, in fact, deviated from its ‘ethical’ commitment and worked as usual ‘profit-making’ organization. This proved another irony of the Ethical Policy in Java and the Netherlands Indies in general.